(untitled) (Research, Society and Development, 2020)
The temporomandibular joint (TMJ) is certainly one of the most complex in the body. From its operation, classification to the origin of the existing dysfunctions that involve it. The etiology of temporomandibular disorders (TMD) is multifactorial and complex, recent studies point to a great relationship between psychological problems and TMD, not as a direct factor, but corroborating with others or working as triggers for signs and symptoms. In the clinical routine, patients with TMJ-related complaints are accompanied by some level of depression and / or anxiety, making the treatment even more comprehensive, requiring the dentist to treat the patient as a whole and not just the TMJ or mouth, referring for other professionals, being a multidisciplinary treatment. In the present work, keywords such as ‘’ temporomandibular disorder ’’, ‘‘ depression ’’ and ‘’ ‘anxiety’ ’were used in the PubMed, BVS and Scielo databases. TMD is still very complex in the literature, mainly to determine the factors that cause it exactly in each patient, so it is important to further studies in this area, seeking a greater elucidation of the topic.